Edina contra Septem ou la résistance à la lutte des étudiantes de médecine d’Édimbourg en 1870 - Christian Auer (Cahiers Victoriens et Edouardiens)
This article aims to study some of the mechanisms of resistance that were implemented by the patriarchal society to oppose the women who, in the course of the second half of the nineteenth century, tried to put an end to the process of marginalisation they were subjected to. The article will focus on the female medical students of Edinburgh in the 1870s since this struggle is representative of the oppositions, conflicts and resistances which characterised relations between sexes at that period. Indeed, by asking to become doctors, Sophia Jex-Blake and her friends were transgressing established rules and challenging the dogmas of masculine superiority and exclusivity. The resistance of the medical community expressed itself particularly through an essentialist discourse that stressed the “inherent” weaknesses of those who aspired to become doctors. This article also points to the ambiguity of the term “patriarchal”. The generic nature of the term conveys the image of a united and compact society of individuals sharing the same timeless ideology. Yet, the different reactions to the struggle of the female medical students of Edinburgh demonstrate that Victorian patriarchal society was diverse rather than monolithic.